Utopia Pengembangan Pariwisata Kabupaten Halmahera Utara - Babua, Piet Hein; Goraph, Frets A.; Djurubassa, Gloria Miagina Palako; Tondo, Simson (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Tourism Development Utopia North Halmahera District) This study examines the development of tourism in North Halmahera Regency through regional clustering. The Tobelo cluster is directed toward marine tourism development, the Galela-Loloda cluster toward the development of lakes, hot springs, and waterfalls, and the Kao-Malifut cluster toward the development of heritage sites, specifically World War II Japanese historical relics. Through qualitative research methods, including observation, interviews, documentation, and data analysis, three indicators of achievement were identified: improved tourist destination infrastructure, effective and efficient marketing brands, and increased quality creative economy groups. Twenty tourism problems were found in three tourism development sectors. However, the development of tourism in North Halmahera Regency has experienced many obstacles due to the pandemic, such as neglected, damaged, dirty, and destroyed tourist infrastructure and a neglected tourist environment. Abstrak Penelitian ini mengkaji tentang pengembangan pariwisata di Kabupaten Halmahera Utara yang menggunakan pembagian klasterisasi wilayah yaitu klaster Tobelo yang diarahkan sebagai kawasan pengembangan wisata bahari, klaster Galela-Loloda yang diarahkan pada pengembangan Danau, Air Panas dan Air Terjun dan Kao-Malifut diarahkan pada pengembangan Heritage (Peninggalan Sejarah Jepang Perang Dunia II). Dengan menggunakan penelitian kualitatif yakni melalui pengamatan (observasi), wawancara, dan dokumentasi serta analisis data, maka di temukan tiga indikator capaian kajian ini, yakni penelitian ini mampu meningkatkan sarana prasarana destinasi wisata, meningkatkan brand pemasaran yang efektif dan efisien serta meningkatkan kelompok ekonomi kreatif yang berkualitas. Dalam kajian ini ditemukan dua puluh permasalahan pariwisata dari 3 sektor pengembangan pariwisata. Namun, akibat Pandemi Covid 19, pengembangan pariwisata Kabupaten Halmahera Utara mengalami banyak kendala, seperti sarana prasarana wisata tidak terurus, rusak, kotor, hancur dan lingkungan wisata tidak terurus.